Mongolia Tourism Sector Policy Note : Strengthening Management of Natural and Cultural Heritage Assets to Scale-up Tourism and Stimulate Local Economic Opportunity - World Bank (Washington, DC, 2017)
This report, Strengthening Management of Natural and Cultural Heritage Assets to Scale-up Tourism and Stimulate Local Economic Opportunity was prepared in March 2011. The principal objective of the assignment is to provide policy guidance to decision-makers for strengthening the management of NCS and building a sustainable tourism industry in Mongolia that enhances economic opportunity, especially for local communities.There are several constraints to faster growth of the tourism sector, including: (i) a harsh climate and short tourist season, which is concentrated in the months of June, July and August; (ii) poor quality of infrastructure; (iii) limited international air access to Mongolia; (iv) poor service quality, which is driven by a lack of industry-led guidelines that promote quality standards, and low awareness on what quality and appropriate service culture is; and (v) limited capacity and lack of experienced tourism workforce.